2017
DOI: 10.1016/j.jfda.2016.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Functional study of Cordyceps sinensis and cordycepin in male reproduction: A review

Abstract: Cordyceps sinensis has various biological and pharmacological functions, and it has been claimed as a tonic supplement for sexual and reproductive dysfunctions for a long time in oriental society. In this article, the in vitro and in vivo effects of C. sinensis and cordycepin on mouse Leydig cell steroidogenesis are briefly described, the stimulatory mechanisms are summarized, and the recent findings related to the alternative substances regulating male reproductive functions are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 74 publications
0
34
0
1
Order By: Relevance
“…Membranes were then washed three times with TBST and incubated for 1 h with the appropriate HRP conjugated secondary antibodies. Bands were detected using ECL substrate and the UVP EC3 BioImaging system (UVP, LLC, Phoenix, AZ, USA) (32)(33)(34). Quantification of the western blotting data was performed using ImageJ version 1.50 software (National Institutes of Health, Bethesda, MD, USA).…”
Section: Chemicalsmentioning
confidence: 99%
“…Membranes were then washed three times with TBST and incubated for 1 h with the appropriate HRP conjugated secondary antibodies. Bands were detected using ECL substrate and the UVP EC3 BioImaging system (UVP, LLC, Phoenix, AZ, USA) (32)(33)(34). Quantification of the western blotting data was performed using ImageJ version 1.50 software (National Institutes of Health, Bethesda, MD, USA).…”
Section: Chemicalsmentioning
confidence: 99%
“…7 Kısaca, Cordyceps preparatları ve bileşiklerinin antikanser, antioksidan, antiinflamatuar ve antimikrobiyal aktivitelerinin yanı sıra hepatik, renal, kardiyovasküler, solunum, sinir, cinsel ve immünolojik sistemlere etkisi dikkate değer bulunmaktadır. 17…”
Section: Farmakoloji̇k Etki̇lerunclassified
“…[15][16][17] Cordycepin (3'-deoxyadenosine; C 10 H 13 N 5 O 3 ) ( Figure 1A), a major bioactive compound of Cordyceps sinensis, has a wide range of biological effects regulating steroidogenesis, inflammation, and platelet aggregation. [18][19][20][21] Besides, studies have shown that cordycepin exerts a large variety of antitumor abilities. 22,23 However, it is rare on the investigation of antitumor effect of cordycepin on testicular tumor.…”
Section: Introductionmentioning
confidence: 99%